Estratégias pedagógicas com uso de tecnologias para o ensino de trigonometria na circunferência - Fernandes, Ricardo Uchoa (2010)
The effective learning of the student is the main goal of a reflective teacher, so it is not enough simply to have all the technical knowledge, you need something more, namely mediation, have a clear and objective, to mobilize material resources for the success of this process . Just thought, this work was to build a meaningful learning the basics of trigonometry in circumference. use this research to teaching engineering, a research methodology that is considered as an experimental scheme based on achievements in teaching classroom. The research has two analytical tools, giving great importance to the training analysis of the error. The first instrument directs for construction of the trigonometric circle, using ruler, protractor and pencil, the second instrument construction is done in dynamic geometry software GeoGebra. The activities of this research tool, as applied to twelve students in the 2nd grade of high school to a state school in Guaratinguetá, interior of Sao Paulo, in the Paraiba Valley. Were two meetings for the application, the students worked individually in the first assessment tool and trio in the second evaluation instrument. The trial shows that prior knowledge have been mobilized to carry out these activities, and information technology as a pedagogical resource, ie, activity with GeoGebra aroused the interest of students because they were more focused and performance was better